2018
DOI: 10.2465/jmps.170420
|View full text |Cite
|
Sign up to set email alerts
|

Amphibole in UHP eclogite from the Sulu region, eastern China

Abstract: We examined the stability of amphibole in ultrahigh-pressure (UHP) conditions of about 620-750°C, 2.9-3.7 GPa based on the mineralogy of UHP eclogites collected from the Qinglongshan and Jianchang areas in Donghai County of the Sulu region. The samples studied are mainly composed of garnet, omphacite, amphibole, rutile, kyanite, quartz, epidote, and phengite. Amphibole can be classified into three types based on its mode of occurrence; Amp I, inclusions in garnet and epidote; Amp II, the matrix phase; Amp III,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Common occurrences of coesite and other UHP index phases indicate that the eclogite, ultramafic rock, and their host gneisses in the Donghai area were extensively recrystallized under the coesite eclogite facies conditions (e.g., Zhang et al, 2005Zhang et al, , 2009; Liu and Liou, 2011). Peak metamorphic conditions for the Donghai area were estimated at 2.2-4.0 GPa/620-880 °C (e.g., Zhang et al, 2000;Li et al, 2011;Yamasaki et al, 2018). Yamasaki et al (2018) systematically studied amphibole-bearing samples from Qinglongshan and Jianchang (Fig.…”
Section: Geological Setting and Petrographymentioning
confidence: 99%
See 2 more Smart Citations
“…Common occurrences of coesite and other UHP index phases indicate that the eclogite, ultramafic rock, and their host gneisses in the Donghai area were extensively recrystallized under the coesite eclogite facies conditions (e.g., Zhang et al, 2005Zhang et al, , 2009; Liu and Liou, 2011). Peak metamorphic conditions for the Donghai area were estimated at 2.2-4.0 GPa/620-880 °C (e.g., Zhang et al, 2000;Li et al, 2011;Yamasaki et al, 2018). Yamasaki et al (2018) systematically studied amphibole-bearing samples from Qinglongshan and Jianchang (Fig.…”
Section: Geological Setting and Petrographymentioning
confidence: 99%
“…Peak metamorphic conditions for the Donghai area were estimated at 2.2-4.0 GPa/620-880 °C (e.g., Zhang et al, 2000;Li et al, 2011;Yamasaki et al, 2018). Yamasaki et al (2018) systematically studied amphibole-bearing samples from Qinglongshan and Jianchang (Fig. 1b) and concluded that sodium-calcium amphibole phases (barroisite-taramite) have been stable under UHP metamorphic stage.…”
Section: Geological Setting and Petrographymentioning
confidence: 99%
See 1 more Smart Citation